2001
DOI: 10.1046/j.1365-2869.2001.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern analysis of sleep‐deprived human EEG

Abstract: Progress during the past decade in non‐linear dynamics and instability theory has provided useful tools for understanding spatio‐temporal pattern formation. Procedures which apply principle component analysis (using the Karhunen–Loeve decomposition technique) to the multichannel electroencephalograph (EEG) time series have been developed. This technique shows localized changes of cortical functioning; it identifies increases and decreases of the activity of localized cortical regions over time while the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
8
2
Order By: Relevance
“…Alpha band activity is thought to represent inhibitory drive from activation of GABAergic synapses from the thalamic projections to the cortex [22]. Alpha (8)(9)(10)(11)(12) activity is also reported to be lower in individuals with chronic pain [9], localized in the insula [2] and frontal electrodes [9], with reduced high alpha (13-15 Hz) activity reported in the frontal electrodes [3]. This pattern of findings indicating abnormal low frequency oscillations between the thalamus and the cortex has been labeled "thalamo-cortical dysrhythmia" [1,23] and may underlie, or at least put individuals at risk for, the experience of pain.…”
Section: Chronic Pain and Eegmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha band activity is thought to represent inhibitory drive from activation of GABAergic synapses from the thalamic projections to the cortex [22]. Alpha (8)(9)(10)(11)(12) activity is also reported to be lower in individuals with chronic pain [9], localized in the insula [2] and frontal electrodes [9], with reduced high alpha (13-15 Hz) activity reported in the frontal electrodes [3]. This pattern of findings indicating abnormal low frequency oscillations between the thalamus and the cortex has been labeled "thalamo-cortical dysrhythmia" [1,23] and may underlie, or at least put individuals at risk for, the experience of pain.…”
Section: Chronic Pain and Eegmentioning
confidence: 99%
“…One issue that has not been addressed is the potential biasing impact of sleep deficits on EEG-measured activity. Sleep deficits are commonly reported by people with chronic pain [8], and the EEG bandwidth markers associated with sleep deprivation have similarities to those associated with chronic pain [3,[9][10][11][12][13][14]. These findings raise important basic questions: 1) Can we distinguish between the contributions of chronic pain and sleep deficits found within the EEG bandwidth power spectrum?…”
Section: Introductionmentioning
confidence: 98%
“…Several studies reported an increase in the degree of correlation between activity in both hemispheres as a result of prolonged wakeful-ness [see e.g., ref. 99 , 100 ]. Furthermore, an anterior shift of activity has been reported after 24 h of wakefulness: the overall power, as well as the power contained in the alpha band, decreased at occipital and temporal channels and increased at central and frontal channels [ 76 ].…”
Section: Spatial Patterns Of the Encephalogrammentioning
confidence: 99%
“…Essentially, a garment disrupts sweat evaporation from the skin surface, and this insufficient evaporation often provides the feel of discomfort found while wearing a garment [26]. during sweating, sweat is released into the environment through the garment.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of sweat evaporation largely depends on the garment that represents a barrier in this process. Essentially, a garment disrupts sweat evaporation from the skin surface, and this insufficient evaporation often provides the feel of discomfort found while wearing a garment . The evaporation rate itself affects comfort that is received through wearing of a certain garment.…”
Section: Introductionmentioning
confidence: 99%